First let's state the given parameters:
Number of Elena's guest = g
The expression Elena wrote on difference in cost of two venues = (62 + 35g) - (56 + 27g)
First venue:
Let the booking fee = B
the Cost per guest = C
We are told the cost of each venue is equal to the sum of the booking fee and the result of the multiplication of number of guest and the cost per each guest.
Let the cost for the first venue = Y
Y = Cg + B
Second venue:
Let the booking fee = A
the Cost per guest = D
Let the cost for the first venue = Z
Z = Dg + C
The difference between the two venues:
(Cg + B) - (Dg + C) (this is the equivalent expression)
In expression presently written, there is no value given. Hence we represented the values with variables. We can see the cost is in the form of a linear expression:
y = mx + c
Also the number of guest is represented by g in the new expression.